The Methylome of Soybean Roots during the Compatible Interaction with the Soybean Cyst Nematode. Issue 4 (22nd June 2015) - Rambani, Aditi; Rice, J. Hollis; Liu, Jinyi; Lane, Thomas; Ranjan, Priya; Mazarei, Mitra; Pantalone, Vince; Stewart, C. Neal; Staton, Meg; Hewezi, Tarek
Abstract : The soybean cyst nematode induces genomewide differential DNA methylation that impacts a large number of structural genes and biological functions. Abstract: The soybean cyst nematode (SCN ; Heterodera glycines ) induces the formation of a multinucleated feeding site, or syncytium, whose etiology includes massive gene expression changes. Nevertheless, the genetic networks underlying gene expression control in the syncytium are poorly understood. DNA methylation is a critical epigenetic mark that plays a key role in regulating gene expression. To determine the extent to which DNA methylation is altered in soybean ( Glycine max ) roots during the susceptible interaction with SCN, we generated whole-genome cytosine methylation maps at single-nucleotide resolution. The methylome analysis revealed that SCN induces hypomethylation to a much higher extent than hypermethylation. We identified 2, 465 differentially hypermethylated regions and 4, 692 hypomethylated regions in the infected roots compared with the noninfected control. In addition, 703 and 1, 346 unique genes were identified as overlapping with hyper- or hypomethylated regions, respectively. The differential methylation in genes apparently occurs independently of gene size and GC content but exhibits strong preference for recently duplicated paralogs. Furthermore, a set of 278 genes was identified as specifically syncytium differentially methylated genes. Of these, we found genes associated with epigenetic regulation, phytohormone signaling, cell wall architecture, signal transduction, and ubiquitination. This study provides, to our knowledge, new evidence that differential methylation is part of the regulatory mechanisms controlling gene expression changes in the nematode-induced syncytium.